A Cross-Section Model of Economic Growth Re-Examined - Kosobud, Richard F.; O'Neill, William D. (The Review of Economics and Statistics, 1972)
Using the same sample of 100 countries for 1966 as Sommers and Suits,3 we obtained the following equation 4 GCF/GNP 26.87 (1.04) 4676.54 / (GNP/N + 300). (629.25) R2= .4 (4) Comparing this result with the estimation of the quadratic equation (1) of Sommers and Suits,5 we see that both equations have similar statistical properties. Using (4) as the basis for simulations of the growth path, however, we obtain completely different results from those of Sommers and Suits. Now per capita income does not attain a stationary level, but grows exponentially. The growth rate of per capita income, however, as can be seen from figure 2, attains a stationary level at 4.41 per cent per year. FIGURE 2. SIMULATED GROWTH RATE OF GNP PER CAPITA